PERAN PROMOTOR KESEHATAN TERHADAP PERILAKU MEMBUANG SAMPAH PADA MASYARAKAT - Wahyusaputra, Muhammad; Ervina, Lissa; Sumaryono, Dino (Poltekkes Kemenkes Bengkulu, 2024)
Garbage is a common problem faced by people all over the world. The World Bank (2018) says that the number of people in the world which is increasing every year is the cause of an increasingly critical waste problem. Countries that are the largest contributors of waste are China, Indonesia, the Philippines, Vietnam and Sri Lanka. In Indonesia, there is 64 million tons of waste per year and is expected to continue to increase every year.How is the role of health promoters on community behavior regarding waste problems in Sawah Lebar Village, Bengkulu City.The research design used is qualitative research, using ethnographic methods. Ethnographic research basically aims to understand or explore life, certain behaviors in a group of people. This research was conducted to obtain in-depth information and to find out the behavior of the community in disposing of waste in the village of rice fields in the city of Bengkulu., which is taken every day using a pick-up car. In a day, the garbage officer picks up trash 2 times a day, every 07.00 WIB and 17.00 WIB. And there are also some who throw garbage directly behind the wide rice field stadium of Bengkulu City.it was concluded that the behavior of the community in throwing garbage in the broad rice field community of Bengkulu city, some wanted it instantly and some directly threw it into the trash can behind the wide rice field in Bengkulu city and some were placed on the side of the road and then taken by the cleaners who use trucks.